Proceso atención de enfermería en paciente de 47 años con absceso intestinal. - Muñoz Sotomayor, Maleni Rocío (2025)
The present clinical case study is applied to a 47-year-old male patient with a surgical history of appendectomy 1 week ago who was admitted to the emergency area due to a clinical picture of ±48 hours of evolution characterized by abdominal pain of great intensity VAS 7/10, hyperthermia, nausea, emesis, hyporexia, general malaise and purulent and fetid discharge at the level of the post-surgical wound. When taking vital signs, alterations in blood pressure (135/79 mmHg) and temperature (38.4 ° C) were evident. In the physical evaluation, a soft, depressed abdomen was found, painful to palpation with an abscess at the level of the post-surgical wound plus abundant discharge of purulent fluid from the appendectomy performed one week ago. A peripheral vein was placed and broad-spectrum antibiotics, antipyretics and analgesics were administered under medical prescription. Complete blood count and abdominal ultrasound were performed. Patient is hospitalized in the internal medicine area due to his infected surgical wound (appendectomy) and diagnosis of intestinal abscess (surgical history). Where the Nursing Care Process will be applied using the Nanda, Noc and Nic taxonomies as a support tool, in order to provide nursing care according to his diagnosis.